Moderate static magnetic fields prevent estrogen deficiency-induced bone loss: Evidence from ovariectomized mouse model and small sample size randomized controlled clinical trial - Shenghang Wang; Jiancheng Yang; Yunpeng Wei; Chao Cai; Shuai Chen; Youde Wu; Xiao Li; Lilei Sun; Xianglin Li; Ming Gong; Jianhua Zhou; Yawei Hu; et al. (PLoS ONE, 2025)
Background Postmenopausal osteoporosis (PMOP) is the most common type of osteoporosis. Numerous studies have shown that static magnetic fields (SMFs) can inhibit bone loss by regulating bone remodeling. However, there are currently no clinical studies on the treatment of osteoporosis with SMFs. This study aims to investigate the clinical therapeutic effects of moderate static magnetic fields (MMFs) on PMOP. Methods In this paper, we constructed MMF device using neodymium-iron-boron (NdFeB) materials. At the animal level, the effect of MMF exposure for 8 weeks on estrogen deficiency-induced bone loss was investigated by evaluating bone microstructure, mechanical properties, and bone conversion using ovariectomized (OVX) mice. Clinically, a single-blind randomized controlled study in patients with PMOP was designed. PMOP patients aged 55–70 years were recruited and randomized into the control and MMF treatment groups. Clinical assessments of bone mineral density (BMD), bone turnover markers (BTMs) and VAS scores were performed at baseline and day 90, respectively. Results The results showed that MMF exposure significantly improved BMD, bone mineral content (BMC), bone microarchitecture and bone strength in OVX mice. For bone turnover, MMF increased the number of osteoblasts on the bone surface of OVX mice as well as the level of serum bone formation marker P1NP, while decreasing the number of osteoclasts and the level of serum bone resorption marker β-CTX. The clinical trial’s results showed that MMF treatment had a positive effect on the improvement of BMD in the lumbar spine and increased serum P1NP levels while decreased β-CTX levels. In addition, MMF treatment decreased participants’ VAS scores for low back pain. Conclusions The results of both animal and clinical studies demonstrated that MMF treatment improved bone turnover and have a positive effect on BMD improvement, as well as alleviated low back pain in PMOP patients. This study will promote the translational research and clinical application of SMF treatment for osteoporosis. Trial registration Intervention study of moderate static magnetic field on osteoporosis and iron metabolism in postmenopausal women, ChiCTR2100048604